Kesejahteraan Psikologis Guru Sekolah Dasar - Kristiyana, Yosi Imas; Fuad, Nurhattati; Rahmawati, Desi; Mayasari, Linda Ika; Takdir, Muh. (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
Teachers are key actors in the success of the educational process; therefore, their psychological well-being is a crucial aspect in supporting the quality of learning. This study aims to describe the level of psychological well-being of elementary school teachers, identify the factors influencing it, and analyze its implications for learning quality and the achievement of the Sustainable Development Goals (SDG 3 and SDG 4). The study employed a mixed-methods approach with the integration of quantitative and qualitative data using a sequential explanatory design. Quantitative data were collected through Ryff’s Psychological Well-Being Scale completed by 19 teachers from two public elementary schools, while qualitative data were obtained through observations and in-depth interviews with five teachers. The results indicate that teachers’ psychological well-being is at a moderate level, with no significant difference in mean scores between schools. The dimensions of purpose in life and personal growth showed higher scores, whereas the dimensions of positive relations and autonomy exhibited greater individual variation. Factors influencing psychological well-being include administrative workload, organizational support, principal leadership, and stress management strategies. These findings emphasize that teachers’ psychological well-being is shaped not only by personal factors but also by school organizational structures and work culture. This study recommends strengthening institutional support and enhancing teachers’ capacity as strategies to improve psychological well-being and educational quality.